2021
DOI: 10.22267/rcia.213801.151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salicylic acid and progesterone on physiological characteristics of Kentucky bluegrass under salinity stress

Abstract: Salinity is one of the most important limiting factors in plant growth. It is also a predominant constraint that impairs grass growth and quality. Plant hormones play important roles in the capability of plants to adapt to environmental stresses. Hence, the impact of two plant growth regulators (PGRs) i.e. salicylic acid (SA) and progesterone (P4) was studied on biological characteristics of Poa pratensis in saline conditions in a greenhouse experimnt. The experimental treatments were composed of salinity at f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It can also be assumed that the impatiens during this period continues to defend itself against ROS by producing a high amount of enzymatic and non-enzymatic antioxidants (Kim et al, 2014). However, numerous studies reported a decline in the activity of antioxidant enzymes in various plants in the final stage of stress (three days or more after exposed plant to stress), indicating that antioxidant capacity and thus drought tolerance can vary among plants (Almeselmani et al, 2006;Sabzmeydani et al, 2021). It is evident that plant response to drought depends not only on the extremity and time duration of the stress but also on the plant genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be assumed that the impatiens during this period continues to defend itself against ROS by producing a high amount of enzymatic and non-enzymatic antioxidants (Kim et al, 2014). However, numerous studies reported a decline in the activity of antioxidant enzymes in various plants in the final stage of stress (three days or more after exposed plant to stress), indicating that antioxidant capacity and thus drought tolerance can vary among plants (Almeselmani et al, 2006;Sabzmeydani et al, 2021). It is evident that plant response to drought depends not only on the extremity and time duration of the stress but also on the plant genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…A soccer field covering an area of about 7,500 square meters was selected as the research object, and the green grass species of the course was grassland early maturing grass [31], the soil was mainly brown soil and brown soil, the thickness is unknown, and the sprinkler irrigation conditions are good. According to the terrain and vegetation growth status, the sample collection area was in the area with a rich vegetation community, the lawn grass grew well, and the sunshine was sufficient.…”
Section: The Current Situation Of the Ecological Benefits Of The Lawn...mentioning
confidence: 99%